Fatores ambientais relacionados à transmissão da leishmaniose visceral em áreas endêmicas às margens do rio Mossoró, no Rio Grande do Norte - Amorim, Camila Fernandes de (2014)
The Visceral Leishmaniasis (VL) is a anthropozoonosis whose occurrence depends on the presence of species involved in the transmission chain and favorable environmental conditions. In the city of Mossoró, Rio Grande do Norte, VL is endemic, and the disease vector, the sandfly Lutzomyia longipalpis species present in significant numbers throughout the year, and its wetlands to development coupled with the presence of organic matter and animals. These factors justify the choice of the areas of this study, near the River Mossoró, being wet and biodiversity areas that may favor the development of the vector. Based on the foregoing, this study aimed to characterize the risk of transmission of VL near the River Mossoró areas in the city of Mossoró, Rio Grande do Norte. The research took place in the districts of Alto da Conceição Ilha de Santa Luzia and Paredões, with 478 residences that are nearby the bed of the Rio Therefore, an entomological survey was conducted with CDC light traps using the methodology employed by the Ministry of Health Brazil and analyzed the influence of temperature, humidity, rainfall and winds over the sandflies captured. Questionnaires with 478 residents of the area was also conducted, addressing the population's knowledge about the LV as well as routine activities of residents and environmental characteristics that could favor the maintenance of the vector. It was observed that sand flies are present in the area throughout the year, and in greater quantity peridomiciles 71.3% (p<0.05). The female L. longipalpis predominate over other species, 92.2% (p<0.05) and the number of males than females was 62.4% (p<0.05). With the questionnaires, it was observed that with respect to social profile, the majority of respondents were female, with ages between 18 and 40 years in education and 53.8% had completed elementary (p<0,05). Still on the responses, 61.5% raised dogs, 95.9% had little knowledge about the characteristics inherent to sandflies and 85.3% were unaware of the environments preferably this vector (p<0.05). The characteristics of the environment, sewage were dumped mainly in the River (44.6%) and 76.6% of the respondents complained about the presence of garbage in the streets accumulation (p<0.05). Associations analyzed, statistical significance between education, knowledge about the transmission of VL and local preference vector (p<0.05), demonstrating that the level of education may influence the population's knowledge about disease transmission. Thus, comparing the vector density to environmental factors, it can be seen that the high temperature and humidity, rainfall and low wind speeds, make the environment conducive for the development of the vector. Regarding the lack of knowledge of the population about the LV and the environment where these people reside, these facts reflect the risk of maintaining the sandfly and consequently in disease transmission. May conclude that the lack of knowledge about the disease and ways to vector control and leave the residents of these areas dogs at risk of infection